Paraprobiotics obtained by six different inactivation processes: impacts on the biochemical parameters and intestinal microbiota of Wistar male rats - Almada, Caroline N.; Almada-Erix, Carine N.; Roquetto, Aline R.; Santos-Junior, Valfredo A.; Cabral, Lucelia [UNESP]; Noronha, Melline F.; Goncalves, Any Elisa S. S.; Santos, Philipe dos; Santos, Andrey dos; Martinez, Julian; Lollo, Pablo C.; Costa, Whyara K. A.; et al. (Taylor & Francis Ltd, 2021)
This study investigated the effects of feeding paraprobiotics obtained by six processes [heat, ultrasound, high pH, low pH, irradiation and supercritical carbon dioxide (CO2)] on biochemical parameters and intestinal microbiota of Wistar male rats. Daily administration of paraprobiotics did not affect (p >= 0.05) the food intake, body weight, glucose and triglycerides levels, expression of antioxidant enzymes or thermal shock proteins in comparison to the control. Bifidobacterium lactis inactivated by irradiation and supercritical CO2 decreased the total cholesterol levels in serum (p < 0.05). Bifidobacterium lactis inactivated by supercritical CO2 increased the albumin and creatinine levels, while decreased the HDL-cholesterol levels (p < 0.05). Clostridiales (45.6-56%), Bacteroidales (31.9-44.2%) and Lactobacillales (3.9-7.8%) corresponded to the major orders in paraprobiotic groups. The properties of paraprobiotics are dependent on the method of inactivation, the intensity of the method employed and on the strain used.
Keywords: Bifidobacterium; Lacticaseibacillus; supercritical CO2; high pH; irradiation; ultrasound